Impact of the Covid-19 Pandemic on Medical Education among Students of Lahore, Pakistan: Medical Students’ Knowledge, Attitudes, and Response Regarding Online Learning - M Usman Sarwar, Usama Arshad, Sumair Nasim Qureshi, Tayaba Tufail, Manqoosh ur Rehman, Shaukat Rabbani, Urooj Sajjad (Pakistan Journal of Medical & Health Sciences, 2022)
Background: COVID-19 was announced as a pandemic issue globally on 11th March, 2020. In response to this situation, all educational activities including medical and clinical education in various colleges across the country were suspended on the 15th of March. So, online education emerged as an alternative method of teaching & learning to maintain continuity of education Aim: To evaluate the use of online learning modalities and to find their feasibility and usability in medical education. Methods: A cross-sectional study was performed across the government and private medical colleges of Lahore. Eligible participants were undergraduate medical students from 10 medical colleges of Lahore. A questionnaire linked to a Google form was distributed to the medical students across 10 government and private medical colleges through different social platforms. Results: A total of 439 valid questionnaires were collected. 31.7% of students disagreed that interaction between students and teachers was possible through online teaching. Only 7.7% of students agreed that online learning can be used for clinical teaching of medical sciences, as compared to 35.8% who disagreed with this answer and 12.8% who were neutral. 23% of the students agreed that online learning was more convenient and flexible than traditional learning, while 24% disagreed and 21.4% were neutral in this regard. Only 19.8% of students had problems with poor internet services. Conclusion: As Pakistan has faced four waves of the COVID-19 which is not over yet due to the emergence of new strains. Due to vaccination of medical students medical education is back to conventional physical learning but online learning has gained importance as an effective alternate to continue learning processes in exceptional situations like COVID-19 pandemic. Keywords: Covid-19 pandemic, online education